Rotated Color Shift Keying for Visible Light Communications With Signal-Dependent Noise - Gao, Qian; Qaraqe, Khalid; Serpedin, Erchin (IEEE communications letters, 2020)
This letter proposes three distinct modulation schemes belonging to the class of rotated color-shift keying (CSK) to improve the performance of regular CSK over a tricolor visible light communications (VLC) channel subject to signal-dependent noise (SDN). In such channels, regular CSK schemes suffer from a severe constellation distortion. The proposed rotated CSK schemes termed respectively separative whitening-like rotation (SWR), multiplicative whitening-like rotation (MWR), and additive whitening-like rotation (AWR), provide error rate gains relative to the regular CSK. The proposed modulations are carried out by employing practical lighting constraints, including a relaxed color constraint by the MacAdam ellipses with appropriate steps.